Um espaço de liberdade?: O compromisso ético-político de estagiários da Clínica-Escola de Psicologia da Universidade Federal do Ceará com a transformação social - Sousa, Luiza Eridan Elmiro Martins de (2023)
This thesis starts from the problematization of the processes involved in the training for the praxis of interns at the Clinic-School of Psychology at the Federal University of Ceará (CEPSI), Fortaleza campus. It takes a look at what a clinical psychologist does from the perspective of Martín-Baró's Socio-historical Psychology and Liberation Psychology, in dialogue with Frantz Fanon. Its justification is to make up for the lack of reflections and articulations on the social dimension of the clinic. Thus, the starting question is: What elements of the clinical praxis of CEPSI interns are capable of providing answers to individual-society questions and enabling processes of social transformation? This led to the main objective of this thesis: Investigating the meanings attributed by interns to clinical praxis at CEPSI regarding the individual-society dialectic and personal and collective transformation. To this end, a brief journey through the history of psychology is presented, which, seeking scientific validation, adopted theories and methods focused on the individual, disregarding the social issues that affect them. The methodology used was qualitative in nature, based on the historical-dialectic materialist method and Socio-historical Psychology, as contributions to everyday investigation. To obtain the data, the following were carried out: documentary survey, observations of the routine and activities of the researched institution, focus groups and individual interviews with CEPSI interns. In the analysis stage, the methodological strategy of Meaning Nuclei (Aguiar, Soares & Machado, 2015) was worked on, an analytical procedure for apprehending social reality, as a contradictory and historical subjective dimension. The composition of the nuclei in syntheses were articulated with the references adopted theories, leading to the “findings” of the research. The results indicated that the experiences of the interns at CEPSI converge to a reality in which clinical praxis emerges as a dialectical process, where the psychologist is called upon to “de-ideologize” and “decolonize” their practices, overcoming the traditional clinical model, recognizing it as a political space for resignification, construction of meanings and resistance to oppression. This can be achieved through the promotion of spaces for speaking, listening and reflection, as essential tools for the construction of a clinic and a transformative praxis, which seeks not only to mitigate suffering, but to promote liberation and autonomy, recognizing social inequalities as central elements in the construction of mental illness. In short, it is possible to consider, based on the historical-dialectical method, on which the theoretical references studied are based, that clinical praxis emerges in the interns' experience as a possibility of a transformation that is, at the same time, singular and collective. The ethical-political commitment to combating injustices that oppress and make people ill appears as a way to overcome the biomedical-positivist model, guiding towards a critical clinical praxis, aware of the social crossings that affect the singularities of the people served, as well as the impact of your actions to transform reality.